Tinjauan Keterlambatan Pengajuan Klaim Pelayanan Rawat Inap Pasien Bpjs Kesehatan Di Rumah Sakit Umum Daerah Harapan Dan Doa Kota Bengkulu Periode Januari-Maret Tahun 2021 - Nikmah, Ulfatun; Putri, Liza; Shintia, Bella (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2021)
The delay in submitting the inpatient claim file is caused by the file the medical record returned from the inpatient ward is incomplete so it must be returned to be completed by the doctor in charge. From the results of interviews with coding officers at the Harapan and Prayer Hospital Bengkulu City in 2021, it is known that in January there were 96 claim files, in February 71 claim files and in March 38 claim files. It is known the delay in submitting BPJS claims specifically for inpatients at Harapan and Doa Hospital Bengkulu City for the January-March 2021 period. The research method is a research method used to examine the condition of natural objects, where the researcher acts as a key instrument, data collection techniques are carried out by triagulation (combined), data analysis is inductive and qualitative results emphasize meaning rather than generalization. Of the 205 claim files returned by BPJS, only a small portion of the files did not match the membership administration, namely 17 (8.2%) files due to inappropriate SEP Numbers, inappropriate treatment classes and inappropriate nursing dates. Of the 205 claim files returned by BPJS, some of the files were incorrect in the selection of diagnostic codes and procedures.